Identification of 1-Aminocyclopropane-1-Carboxilid Acid (ACC)-Deaminase Producing Endophytic Bacteria from Local Agricultural Plantation Based on 16S Ribosomal RNA Gene as Genetic Marker - Rumella Simarmata; Ngadiman Ngadiman; Muhammad Saifur Rohman; Partomuan Simanjuntak (Biotropic : The Journal of Tropical Biology, 2019)
The objective of this work was to isolate and identify of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase producing endophytic bacteria from root of local agricultural plantation by using 16S rRNA gene as genetic marker. Twelve root samples were collected from local agricultural plantation in Java area. After surface sterilization, each root sample was inoculated in nutrient agar media and the grown colonies were further purified and tested for the ability to grow in N-free minimal medium containing AIB as a sole of nitrogen source. The selected colonies were further tested for their ACC deaminase activity by measuring the rate of conversion of ACC into α-ketobutyrate. From this work, 12 bacterial strains that exhibited the ACC deaminase activity by 123.75 to 1461.44 nmol α-ketobutyrate/mg/hour were successfully isolated. Based on the 16SrRNA gene sequences, those bacterial isolates were identified as Sphingobacterium multivorum BK1, Bacillus mycoides CB2, Pantoea dispersa CK4, Pantoea agglomerans KD6.2, Enterobacter ludwigii KW3, Bacillus aryabhattai TW7, Pseudomonas monteilii KS12, Pseudomonas plecoglossicida KS16.2, Pseudomonas putida PIR3C, Stenotrophomonas maltophilia PIR5, Lysinibacillus pakistanensis PIC5, and Raoultella terrigena PCM8. Pseudomonas putida PIR3C and Pseudomonas monteilii KS12 showed promising ACC deaminase activity and therefore it could be as a good candidate for further application in plant growth promoting in stress conditions.